Patient-Centered Endodontic Outcomes: A Narrative Review - Hamedy, Reza; Shakiba, Bita; Fayazi, Sara; Pak, Jacklyn G; White, Shane Newport (Iranian Endodontic Journal, 2013)
Introduction: Root canal treatment (RCT) success criteria inform us of the path to bony healing and of prognostic factors, but tell little about how the patient perceives, feels, or values RCT. Patients choose, undergo, and pay for RCT, they live with the result, and inform their community. The purpose of this narrative review was to appraise patient-centered outcomes of initial non-surgical RCT and nonsurgical retreatment, in adults. Materials and Methods: Patient-centered RCT outcome themes were identified in the extant literature: quality of life, satisfaction, anxiety, fear, pain, tooth survival and cost. Narrative review was applied because the disparate themes and data were unsuited to systematic review or meta-analysis. Results: Application of the Oral Health Impact Profile (OHIP) demonstrated that disease of pulpal origin affects quality of life with moderate severity, primarily through physical pain and psychological discomfort, and that RCT results in broad improvement of quality of life. Satisfaction with RCT is extremely high, but cost is the primary reason for dissatisfaction. Anxiety and fear affect RCT patients, profoundly influencing their behaviors, including treatment avoidance, and their pain experience. Fear of pain is “fair” to “very much” prior to RCT. Pain is widely feared, disliked, and remembered; however, disease of pulpal origin generally produces moderate, but not severe pain. RCT causes a dramatic decrease in pain prevalence and severity over the week following treatment. Survival rates of teeth after RCT are very high; complication rates are low. Cost is a barrier to RCT, but initial costs, lifetime costs, cost effectiveness, cost utility, and cost benefit all compare extremely well to the alternatives involving replacement using implants or fixed prostheses. Conclusion: Dentists must strive to reduce anxiety, fear, experienced and remembered pain, and to accurately inform and educate their patients with respect to technical, practical and psychosocial aspects of RCT.